Expression Profiles of 12 Late Embryogenesis Abundant Protein Genes from Tamarix hispida in Response to Abiotic Stress. (10th July 2014) - Gao, Caiqiu; Liu, Yali; Wang, Chao; Zhang, Kaimin; Wang, Yucheng
Abstract : Twelve embryogenesis abundant protein ( LEA ) genes (named ThLEA-1 to -12 ) were cloned from Tamarix hispida . The expression profiles of these genes in response to NaCl, PEG, and abscisic acid (ABA) in roots, stems, and leaves of T. hispida were assessed using real-time reverse transcriptase-polymerase chain reaction (RT-PCR). These ThLEAs all showed tissue-specific expression patterns in roots, stems, and leaves under normal growth conditions. However, they shared a high similar expression patterns in the roots, stems, and leaves when exposed to NaCl and PEG stress. Furthermore, ThLEA-1, -2, -3, -4, and -11 were induced by NaCl and PEG, but ThLEA-5, -6, -8, -10, and -12 were downregulated by salt and drought stresses. Under ABA treatment, some ThLEA genes, such as ThLEA-1, -2, and -3, were only slightly differentially expressed in roots, stems, and leaves, indicating that they may be involved in the ABA-independent signaling pathway. These findings provide a basis for the elucidation of the function of LEA genes in future work.